Induction of Mixed Chimerism Using Combinatory Cell-Based Immune Modulation with Mesenchymal Stem Cells and Regulatory T Cells for Solid-Organ Transplant Tolerance - Im, Keon-Il (Mary Ann Liebert, Inc., 2014)
Establishment of mixed chimerism is an ideal approach to induce donor-specific tolerance while expanding its potential in various clinical settings. Despite the developments in partial conditioning regimens, improvements are still needed in reducing toxicity and bone marrow transplantation-related complications. Recently, cell-based therapies, including mesenchymal stem cells (MSCs), have been incorporated in establishing noncytoreductive mixed chimerism protocols; however, its efficacy is only partial and shows reversed immunosuppressive properties. This study demonstrates a novel approach to induce mixed chimerism and tolerance through combinatory cell-based immune modulation (CCIM) of MSCs and regulatory T cells (Tregs). We hypothesize that the interaction between these cells may lead to greater inhibition of host immune responses. Compared with single cell therapy, CCIM induced a higher engraftment rate and robust donor-specific tolerance to skin allografts across full major histocompatibility complex barriers. These regulatory effects were associated with inhibition of natural killer cell cytotoxic activity, CD4(+)IL-17(+) cells, memory B cells, plasma cells, and immunoglobulin production levels along with increased frequencies of CD4(+)Foxp3(+) cells, IL-10-producing mature B cells, and myeloid-derived suppressor cells. Furthermore, CCIM was able to regulate mortality in a graft-versus-host disease model through reciprocal regulation of Treg/Th17. Taken together, we suggest CCIM as a clinically applicable strategy for facilitating the induction of mixed chimerism and permanent tolerance.